The relationship between life satisfaction and job satisfaction : Evidence from Türkiye using life satisfaction survey - Alabod, Fares (My University, 2024)
Bu çalışma iş tatmini ile yaşam tatmini arasındaki ilişkiyi incelemektedir. Türkiye İstatistik Kurumu tarafından yürütülen Yaşam Memnuniyeti Anketi'ni ve potansiyel yanlılıkları ele almak için Heckman seçim modelini kullanarak. Çalışma bulguları, iki değişken arasında pozitif bir ilişkiyi destekleyen ampirik kanıtlar sunmaktadır. Bu, anlamlı işlere katılmanın ve destekleyici durumlarda bulunmanın genel yaşam memnuniyetini artırmaya büyük ölçüde katkıda bulunduğunu göstermektedir. Bu çalışma, çalışanların memnuniyeti ve refahına bütünsel bir yaklaşımı teşvik eden organizasyonel strateji ve politikaların önemini vurgulayarak, iş tatmini ile genel yaşam tatmini arasındaki ilişkiye dair anlayışımızı geliştirmektedir.

This research examines the relationship between job satisfaction and life satisfaction. By using the Life Satisfaction Survey conducted by the Turkish Statistical Institute and implementing the Heckman selection technique to correct for any biases. The study findings provide empirical evidence that supports a positive relationship between the two variables. This suggests that participating in meaningful work and being in supportive situations greatly contribute to enhancing overall life satisfaction. This study improves our understanding of the relationship between job satisfaction and overall life satisfaction, emphasizing the importance of organizational strategies and policies that promote a holistic approach to employee contentment and welfare.
Keywords: Çalışanlar; Employees; Heckman Seçim Modeli; Heckman Selection Model; İş Memnuniyeti; İş tatmini; İş-Yaşam Dengesi; Job satisfaction; Memnuniyet; Satisfaction; Türkiye; Türkiye Life Satisfaction; Work-Life Balance; Yaşam Memnuniyeti